Result of Under Conceptualized Implementation of Activity and Future Improvements - Mahajan, Hema; Kannaiah, Ch.; Sravani, M. (Journal of Engineering Education Transformations, 2018)
Today education is more focused towards student - centric learning. There are different kinds of learning among one is active learning. Several pedagogical initiatives exist for different kinds of learning. The one such method experimented in class in One Minute Paper(OMP).OMP is an effective technique for evaluating student understanding and reaction to the course material. Apart the instructor can understand what part of the concept was not addressed effectively.Research informs a discussion on how practical implementation techniques can be used to maximize the benefit. Further experimented OMP with intimation and without intimation and its results were specified.